Nitrofurantoin enteric pellets with high bioavailability based on aciform crystalline formation by wet milling. (June 2015) - Yu, Hongxia; Pan, Lei; Li, Pucheng; Zhang, Keru; Lin, Xia; Zhang, Yu; Tang, Xing
Abstract The aim of the present study was to grind nitrofurantoin (NF) with HPMC solution and to determine the dissolution and bioavailability of the enteric pellets prepared with the NF cogrounds and other excipients. During milling, crystalline transformation occurred – the aciform microcrystalline monohydrate II replaced the coarse crystal anhydrate β and the particle size markedly reduced. In vitro test demonstrated that the enteric pellets prepared with NF cogrounds (4 h) revealed a faster dissolution than the commercial tablet and 50% was released within 30 min in the basic medium. Finally, an in vivo test was conducted in beagle dogs. The Cmax and AUC(0→24) of the pellets were 2.19 ± 0.74 μg/ml and 6.73 ± 4.71 μg/ml h, respectively, while the corresponding values were 0.49 ± 0.42 μg/ml and 1.38 ± 1.17 μg/ml h for the tablet. Thus, the bioavailability of the pellets was increased significantly. In conclusion, the wet grinding that reduced the particle size and created the microcrystalline played a major role in the acceleration of the dissolution of NF and, consequently, enhanced the bioavailability, and the wet grinding process offers an alternative approach to improve the dissolution and bioavailability of drugs with poor aqueous solubility.